2009
DOI: 10.2147/vhrm.s3141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin receptor blockade on endothelial function: focus on olmesartan medoxomil

Abstract: Endothelial dysfunction is the common link between cardiovascular disease risk factors and the earliest event in the cascade of incidents that results in target organ damage. Angiotensin II, the terminal pressor effector arm of the renin-angiotensin-aldosterone system, increases blood pressure (BP) by vasoconstriction and sodium and fluid retention, and has a pro-oxidative action that induces endothelial dysfunction and contributes to vascular remodeling. Angiotensin receptor blockers (ARBs) reduce BP and morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 110 publications
1
23
0
5
Order By: Relevance
“…In contrast to this, dedifferentiation in the SMCs of afferent arterioles in our study is not considered to be induced by endothelial damage. A great deal of evidence has suggested that ARBs have protective effects on endothelial cells in both humans and animals, 16,17 and we found almost no morphological abnormalities in endothelial cells in the juvenile and the adult SHR+ARB groups under electron microscopy. None of the rats with these arteriolar lesions had hypertension.…”
Section: Discussionsupporting
confidence: 46%
“…In contrast to this, dedifferentiation in the SMCs of afferent arterioles in our study is not considered to be induced by endothelial damage. A great deal of evidence has suggested that ARBs have protective effects on endothelial cells in both humans and animals, 16,17 and we found almost no morphological abnormalities in endothelial cells in the juvenile and the adult SHR+ARB groups under electron microscopy. None of the rats with these arteriolar lesions had hypertension.…”
Section: Discussionsupporting
confidence: 46%
“…[17][18][19] ARBs are known to dilate efferent arterioles more than afferent arterioles, and to improve glomerular hypertension because AT-1 receptors exist more abundantly in the former. 20 Reports on the nephro-protective effects of ARBs are diverse in methodology; [20][21][22][23][24][25][26][27] however, few studies have concentrated on the morphology of afferent and efferent arterioles. In this study, we examined the morphology of rat renal tissue and noted a marked improvement in glomerular lesions and tubular protein casts in the ZFR+ARB group.…”
Section: Discussionmentioning
confidence: 99%
“…A-II increases blood pressure by vasoconstriction and sodium and fluid retention and produces overt oxidative stress resultant from the activation of NADPH oxidase, a source of ROS in blood vessels, that promotes endothelial dysfunction, inducing cytokines, chemokines and adhesion molecules secretion and contributes to vascular remodeling (Dai, D.Z. & Dai, Y., 2010;Ferrario, 2009;Partigulova & Naumov, 2010). The A-II effects on gene expression are mediated, at least in part, through the cytoplasmic NF-kB transcription factor.…”
Section: Angiotensin-iimentioning
confidence: 99%